Recent Advances on Quinazoline 2023
DOI: 10.5772/intechopen.1001898
|View full text |Cite
|
Sign up to set email alerts
|

Triazoloquinazoline: Synthetic Strategies and Medicinal Importance

Tooba Jabeen,
Sana Aslam,
Matloob Ahmad
et al.

Abstract: Triazoloquinazoline is a fused heterocyclic nucleus, formed by the fusion of two fundamental heterocyclic moieties; triazole and quinazoline. This class of compound is known for its potential as a therapeutic agent and is endowed with several pharmacological applications. Triazoloquinazoline and its derivatives have shown a variety of biological applications such as anticancer, anti-inflammatory, antimicrobial, antiviral, antihypertensive, anticonvulsant, antidiabetic, antioxidant, adenosine receptor antagonis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
51
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(51 citation statements)
references
References 69 publications
0
51
0
Order By: Relevance
“…Triazoloquinazoline represents polyazaheterocycle, which consists of triazolo moiety fused to a quinazoline ring. Its derivatives are widely known as an important class of heterocyclic aromatic compounds for various pharmaceutical applications [1,2]. Moreover, triazoloquinazolines provide a promising molecular platform for materials sciences.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Triazoloquinazoline represents polyazaheterocycle, which consists of triazolo moiety fused to a quinazoline ring. Its derivatives are widely known as an important class of heterocyclic aromatic compounds for various pharmaceutical applications [1,2]. Moreover, triazoloquinazolines provide a promising molecular platform for materials sciences.…”
Section: Introductionmentioning
confidence: 99%
“…The quinazoline component has been explored in the context of fundamental research [3][4][5], with some quinazoline derivatives revealed to have potential application in optoelectronics [6][7][8][9], detection of analytes [10,11], bioimaging [12], etc. [1,2,4]Triazole derivatives, in turn, are considered as blue phosphorescent, TADF emitters or host materials for OLED devices [13][14][15]. Other D-π-A-π-D structures with a triazole ring as an acceptor part show strong emission in solution and potential for optoelectronic purposes [16,17].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations